Venotonics and Anticoagulants-undisclosed Potential of Drug Treatment of Chronic Venous Insufficiency - Olga Pashanova (Journal of Global Pharma Technology, 2016)
This work aims to conduct a comparative analysis of anticoagulant and venotonic therapy for different groups of patients with a diagnosis of acute venous venous thrombosis of the lower extremities. The tasks included the development of anticoagulants and venotonics combinations and dosages for treatment of a) alleviate an existing disease in a patient; b) disease prevention. Rivaroxaban showed the results of a higher recanalization level of the lower extremities veins in patients compared with warfarin. The maximum recanalization indicators of lower extremities veins, the blood flow velocity in them, and the severity of clinical symptoms were obtained for a group of patients taking a combination of rivaroxaban and diosmin.Keywords: Acute venous insufficiency; Venotonics; Anticoagulants; Vein recanalization; Warfarin; Rivaroxaban; Diosmin.